Image-Based Position Control for Three-Wheel Omni-Directional Robot - Sri Sukamta; Anan Nugroho; Subiyanto Subiyanto; Rizal Rezianto; Muhammad Febrian Soambaton; Agus Ardiyanto (Universitas Ahmad Dahlan, 2024)
Robotic technology continues to advance, but real-time position tracking of robot movements still faces challenges, especially in dynamic and irregular environments. Sensors often fail to maintain accuracy due to environmental disturbances. This study introduces an innovation using omnidirectional wheels on a three-wheeled robot and image-based position control to improve maneuverability and precision. This method utilizes an infrared camera mounted on the ceiling to detect the robot's position. Image processing algorithms are used to determine waypoints and direct the robot. Omni-directional wheels allow the robot to move freely in all directions, which is important for accurate navigation on complex trajectories. The robot was tested on the